Presentación del proyecto: guía metodológica para la implantación de una biblioteca digital universitaria - Ferrer Sapena, Antonia; Lloret Romero, Nuria (Revista General de Información y Documentación, 2002)
This article introduces work carried out by the Department of Documentation and History of Art at the Universidad Politécnica de Valencia, the Library at this university and the Florida Centre de Formació university Library; the work is the result of a project funded by the Secretaría de Estado de Universidades and is now accessible at http://www.biblioteca-digital.net. The work starts from the scant written, standardized information on the planning and setting up of digital libraries available in this country. Owing to its being a matter of great interest at the present time and of growing use in teaching, it was thought appropriate to approach the subject from a practical viewpoint. The following topics are described and developed: Analysis of the initial condition at the center. Auto evaluation Project planning methodology. Study of costs of setting up a digital library. Study of possibilities of collaborative work with consortiums and with the different member libraries. Legal requirements for the setting up of a digital library system. The conclusion reached is that there is a need for more experience in the field of digital libraries and the professional community is encouraged to make suggestions about the project.
Keywords: Digital libraries; University libraries; Planning; Digitalization